Pengembangan Buku Saku Tembang Dolanan Upaya Penguatan Pendidikan Karakter Cinta Tanah Air - ., Shania Anindya Aciemsha; ., Ludfi Arya Wardana; ., Shofia Hattarina (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
This study aims to produce a pocket book development product called Tembang Dolanan to improve students' love of the motherland character education, which meets valid, efficient, and effective criteria. This research is a Research and Development (R&D) development design, in which the outline of this research flow is (1) research and information collection for initial data needs or needs analysis (need assessment) researchers use observation of student learning activities and distributing questionnaires to teachers and students, (2) initial product development planning in the form of pocket book printing media by considering material, design, subject matter limitations, and preparing trial plans, (3) expert evaluation, carried out by material experts and media experts, (4) revision of results expert evaluation, (5) product trials using 22 research subjects, (6) the final product in the form of Tembang Dolanan pocket book printing media. The material expert validation results reached 93.18% with revisions. Media expert validation results reached 83.33% with revisions. And after the field test the results of the teacher's response reached 91.66% while the results of the student's response reached 100%. Based on these results, the Tembang Dolanan pocket book teaching materials are included in the valid, efficient, and effective qualifications used in learning.